2021
DOI: 10.1021/acsomega.1c00410
|View full text |Cite
|
Sign up to set email alerts
|

Oligonucleotide-Based Reusable Electrochemical Silver(I) Sensor and Its Optimization via Probe Packing Density

Abstract: We report herein a selective, sensitive, and reusable electrochemical sensor for the detection of silver(I) ions. This sensor detects Ag + through a structure-switching electrode-bound DNA by measuring the changes in the electron-transfer efficiency. A single-stranded DNA, featuring a methylene blue (MB)-tagged DNA hairpin structure, strategically provides selective binding for the silver-mediated coordination of cytosine–Ag + –cytosine complexes. The DNA-modified … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…3 B, the system with the highly modified SCGS showed the lowest signal gain, 738, the loosely modified SCGS showed 1586%, and mediumly modified SCGS showed the highest signal gain, 3209, which might be due to the conformation of the oligonucleotide. The oligonucleotide modified with high concentration can occur a 'standing-up' conformation on the surface of the substrate [37] , [38] . Speculatively, for the proposed DNA walker, the oligonucleotide highly modified on the SCGS kept a 'standing-up' conformation (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…3 B, the system with the highly modified SCGS showed the lowest signal gain, 738, the loosely modified SCGS showed 1586%, and mediumly modified SCGS showed the highest signal gain, 3209, which might be due to the conformation of the oligonucleotide. The oligonucleotide modified with high concentration can occur a 'standing-up' conformation on the surface of the substrate [37] , [38] . Speculatively, for the proposed DNA walker, the oligonucleotide highly modified on the SCGS kept a 'standing-up' conformation (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The next example of electrochemical detection of silver ions is a ssDNA oligonucleotide-based sensor proposed by Kim [ 74 ]. The presence of Ag + influences the conformation of the DNA strand and thus changes the electron transfer efficiency.…”
Section: Aptasensors For Metal Ions Detectionmentioning
confidence: 99%
“…Previously, Prof. Han's group suggested that aptasensors detect silver ions via probe packing density [57]. Their approach involved the use of cytosine-rich oligonucleotides (CRO) tagged with methylene blue, which were self-assembled onto the gold electrode surface via thiol groups from the aptamer's 5 ′ -terminal.…”
Section: Introductionmentioning
confidence: 99%